Developing educative snake and ladder learning media to improve understanding on living creature concept - Winarti Agustina; Hapidin Hapidin; Tuti Tarwiyah (Universitas Pendidikan Ganesha, 2018)
The objective of this research was to develop educative snake and ladder learning media to improve the understanding on concept of living creature on early childhood. The research was conducted in Bekasi municipality with R&D method. The results indicated that in aspects of (1) availability of learning media: 75% of teachers used the learning media optimally and 67% of teachers perceived that the learning media made available by the school was less supportive to the learning: (2) requirement: only 25% of teachers who used the game media in learning and 83% of teachers recognized that the learning material in theme books was very supportive to use the media; (3) process: 83% of teachers had difficulty to present the learning material due to children characteristics which are active and aggressive and 75% of teachers recognized that the children’s understanding level regarding the media presented was still low; expectation: 92% of teachers supported the making of educative snake and ladder learning media. Tests administered to the students regarding the living creative concept obtained average score 52,44, which means insufficient.